2016
DOI: 10.1097/nna.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Building a Culture of Inclusion

Abstract: Administrators at Rush University Medical Center have made a commitment to diversity, including accommodating disabilities in the workplace and for students. This article explains extensive multilevel accommodations instituted by Rush University Medical Center that promote organizational growth and a healthier work environment and improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Accounts of disability inclusion champions are relatively uncommon, yet champions are central to existing models for changing corporate culture (Waxman, 2017). Actualizing the strategic advantage attributed to disability inclusion, however, requires a more comprehensive commitment to change attitudes and practices across the organization (Ailey et al , 2016; Kalargyrou, 2014). One key takeaway is that champions play a pivotal role in all stages of building, sustaining, and growing disability inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounts of disability inclusion champions are relatively uncommon, yet champions are central to existing models for changing corporate culture (Waxman, 2017). Actualizing the strategic advantage attributed to disability inclusion, however, requires a more comprehensive commitment to change attitudes and practices across the organization (Ailey et al , 2016; Kalargyrou, 2014). One key takeaway is that champions play a pivotal role in all stages of building, sustaining, and growing disability inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…More concretely, growing inclusion refers to the implementation and evolution of formalized plans to recruit, retain and support the advancement of people with disabilities (Moore et al , 2017). It may include hiring diversity and inclusion professionals or dedicating staff time specifically to disability inclusion work (Ailey et al , 2016). Growth is perhaps the most indeterminate stage of diversity and inclusion initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research studies (Aaberg, 2012;Ailey et al, 2016;Kritsotakis et al, 2017;Luckowski, 2016;Neal-Boylan & Guillett, 2008a;2008b;Neal-Boylan, Fennie & Baldauf-Wagner, 2011;Neal-Boylan, 2012;Neal-Boylan et al, 2012) revealed that nurses were unaware of the requirements of the ADA or how they might be violating them by discriminating against nurses with disabilities. The studies that followed (Davidson et al, 2016;Neal-Boylan & Miller, 2015;Neal-Boylan & Miller, 2017;Neal-Boylan, Miller & Bell, 2018;Neal-Boylan, 2019;Shpigelman & Zlotnick, 2016) focused on increasing that awareness.…”
Section: Students With Disabilitiesmentioning
confidence: 99%
“…RUMC is mentioned as setting the standard of excellence in America. (Ailey et al, 2015) How an Employee should address discrimination complaints- If an employer comes to know that discrimination or victimisation is being practiced because of someone's disability, ideally they should not wait for a complaint to be launched.  An employee should be given the choice to discuss the matter whether formally or informally, Taking a 'Positive Action'-Under the Equality Act, an employer can take 'positive action' to help employees or job applicants it thinks:…”
Section: Employmentmentioning
confidence: 99%